PERAN PEREMPUAN DALAM OPTIMALISASI RANTAI DISTRIBUSI JAGUNG PIPIL UNTUK PENINGKATAN PENDAPATAN PETANI DI KECAMATAN MALANGKE BARAT - Rosnina, Rosnina; Boceng, Annas; Sapareng, Sukriming; Arzam AR, Taruna Shafa; Nuryanti, Dewi Marwati; Halid, Irwan; Anggraini, Aqsyah (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
The distribution of shelled corn in West Malangke District is dominated by intermediaries, resulting in a low farmer's share received by farmers, especially women farmers. This study aims to identify the role of women in the shelled corn distribution chain, analyze marketing margins, and evaluate the profit-to-cost efficiency of each distribution channel in West Malangke District. The results indicate four trading channels, with Channel I as the primary channel, where the highest marketing margin was recorded at IDR 325 per kg, but the lowest farmer's share was only 92.58%. Conversely, Channel IV, which eliminates the role of intermediaries, provided a farmer's share of 100%. The highest profit-to-cost ratio was achieved by village collectors in Channel I (0.68), while wholesalers had a relatively stable profit ratio across channels. These findings suggest that the shorter the distribution chain, the greater the profits received by farmers. The implications of this study emphasize the importance of shortening the distribution chain and empowering women farmers through more efficient market access, as well as the need for policies to improve trading efficiency to support farmer welfare.